Edith Wharton in context - Rattray, Laura (Cambridge University Press, 2012)
"Edith Wharton was one of America's most popular and prolific writers, becoming the first woman to win the Pulitzer Prize for Fiction in 1921. In a publishing career spanning seven decades, Wharton lived and wrote through a period of tremendous social, cultural, and historical change. Bringing together a team of international scholars, this volume provides the first substantial text dedicated to the various contexts that frame Wharton's remarkable career. Each essay offers a clearly argued and lucid assessment of Wharton's work as it relates to seven key areas: life and works, critical receptions, book and publishing history, arts and aesthetics, social designs, time and place, and literary milieux. These sections provide a broad and accessible resource for students coming to Wharton for the first time while offering scholars new critical insights. Of interest to English and American studies departments, the volume will also appeal to researchers in gender studies, film studies, book history, art history, and transatlantic studies"--